The Influence of Social Capital, Entrepreneurial Education Orientation, and Innovation on Business Performance in MSMEs Laundry Businesses in Jakarta - Jonatan, Willy; Widjaja, Oey Hannes (Edumaspul: Jurnal Pendidikan, 2025)
The purpose of this study is to examine the effect of social capital, entrepreneurial orientation, and innovation on business performance. The theory used in this study is the Resource-Based View (RBV) theory, which is defined as high-value, scarce, difficult to imitate, and irreplaceable company resources that can optimize sustainable company competitiveness to produce maximum performance. The method used in this study is a quantitative research method with a sample size of 160. This study used non-probability sampling with purposive sampling technique. Data analysis used the SEM-PLS method and SmartPLS version 4 application, with two stages, namely outer model and inner model testing. The results showed that social capital, entrepreneurial orientation, and innovation had a positive and significant effect on business performance.